A rare case of Wild-Type GIST of descending colon with GANT characteristics - Dimitrios N. Kalliouris; Efstathios Nikou; Spiridon Zaravinos; Konstantinos Manesis; Christianna Oikonomou; Antonina Lingria; Andreas Karameris; Georgios Alexandrakis; Panagiotis Skandalakis; Dimitrios Filippou (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kalliouris DN, Nikou E, Zaravinos S, Manesis K, Oikonomou C, Lingria A, et al. A rare case of Wild-Type GIST of descending colon with GANT characteristics. Turk J Gastroenterol 2019; 30(6): 573-5